2020
DOI: 10.1080/15538362.2020.1717403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Pretreatment on Drying Kinetics and Physio-chemical Characteristics of Yellow European Plums

Abstract: Drying of plums to prunes is an important postharvest processing step, as it results in a product with higher nutrient density, increased shelf life, and significantly greater antioxidant and fiber content. However, due to the waxy layer present on the plums surface having low permeability toward moisture, plum dries very slowly which is an energy-demanding process. Therefore, to breakdown waxy layer on the surface and enhancement of skin moisture diffusivity, two genotypes (V91074 and V95141) of Yellow Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 52 publications
6
27
0
2
Order By: Relevance
“…A reduction in drying time 10, 6.67, and 4.76% in each temperature interval also observed. Similar drying behavior for the influence of drying temperature on drying time has been reported for yellow European plums (Brar et al, 2020), cocoyam slices (Afolabi et al, 2015), and stone apple slices (Rayaguru and Routray, 2012). The present study results were in good agreement with the findings of Vardin and Yılmaz (2018), who reported that the moisture content of hot-water blanched pomegranate arils reached 16% (wb) in 168, 204 and 237 min at 75, 65, and 55°C, respectively.…”
Section: Drying Characteristicssupporting
confidence: 75%
See 4 more Smart Citations
“…A reduction in drying time 10, 6.67, and 4.76% in each temperature interval also observed. Similar drying behavior for the influence of drying temperature on drying time has been reported for yellow European plums (Brar et al, 2020), cocoyam slices (Afolabi et al, 2015), and stone apple slices (Rayaguru and Routray, 2012). The present study results were in good agreement with the findings of Vardin and Yılmaz (2018), who reported that the moisture content of hot-water blanched pomegranate arils reached 16% (wb) in 168, 204 and 237 min at 75, 65, and 55°C, respectively.…”
Section: Drying Characteristicssupporting
confidence: 75%
“…Similarly, a decrease in ascorbic acid for treated and untreated Yellow European plums drying at higher temperature (70°C) has reported by Brar et al (2020). Besides, ascorbic acid pretreated plum samples showed a higher ascorbic acid content as compared to citric acid and potassium metabisulfite pretreatments.…”
Section: Ascorbic Acidsupporting
confidence: 58%
See 3 more Smart Citations